1995
DOI: 10.1128/jcm.33.12.3300-3303.1995
|View full text |Cite
|
Sign up to set email alerts
|

Importance in diagnosis of gastritis of detection by PCR of the cagA gene in Helicobacter pylori strains isolated from children

Abstract: The cagA gene has been detected by PCR and DNA hybridization in 45 Helicobacter pylori strains isolated from children. For each child, clinical symptoms, endoscopic aspect of the gastric mucosa, and histological gastritis were evaluated. Gene-positive strains were associated with hemorrhagic gastritis in 66.6% of the children, while gene-negative strains were associated with hemorrhagic gastritis in 11.2% of the children (P ‫؍‬ 0.0001). In addition, 88.8% of gene-positive strains were associated with severe hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
4

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 19 publications
4
32
0
4
Order By: Relevance
“…37 It is known that the mean serum pepsinogen I level, duodenal ulcer rate, and inflammation score were significantly greater in children infected with cytotoxic H. pylori strains. 38,39 Actually, some investigators have stated that RAP was observed more frequently in pediatric patients with Cag A-positive H. pylori. 39,40 The authors explain this phenomenon by claiming that Cag A-positive strains may favor the local release of neuromediators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 It is known that the mean serum pepsinogen I level, duodenal ulcer rate, and inflammation score were significantly greater in children infected with cytotoxic H. pylori strains. 38,39 Actually, some investigators have stated that RAP was observed more frequently in pediatric patients with Cag A-positive H. pylori. 39,40 The authors explain this phenomenon by claiming that Cag A-positive strains may favor the local release of neuromediators.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Actually, some investigators have stated that RAP was observed more frequently in pediatric patients with Cag A-positive H. pylori. 39,40 The authors explain this phenomenon by claiming that Cag A-positive strains may favor the local release of neuromediators. 40 At the same time, other researchers have not found any abdominal complaints specific for Cag A-and Vac A-positive and Cag A and Vac A-negative H. pylori-infected children.…”
Section: Discussionmentioning
confidence: 99%
“…M olecular typing methods such as ribotyping [1] and randomly amplified polymorphic DNA (RAPD) analysis [2] have demonstrated considerable genomic diversity among Helicobacter pylori isolates. During the past few years, numerous PCR assays have been developed for the identification of specific virulence genes in H. pylori including ureA [3][4][5][6], ureC [7,8], cagA [3,4,9], vacA [10][11][12][13][14][15][16] and the 16S rRNA genes [17,18]. Recently, we have described a method for the rapid simultaneous molecular identification and subtyping of H. pylori by pyrosequencing of the 16S-rDNA variable V1 and V3 region [19].…”
mentioning
confidence: 99%
“…A number of studies are available in the literature on the serum prevalence of the anti– H. pylori antibodies PGA and PGC in unselected children [12,17–19]. However, very few evaluations have been made of the prevalence of H. pylori strains in infected children or of their influence on the grade of gastritis and the circulating levels of anti– H. pylori antibodies or pepsinogens [29]. The aims of our study, therefore, were first to study in a selected population of children the H. pylori genotype and its association with the presence and degree of gastritis, abdominal pain, and the circulating anti– H. pylori antibodies, PGA and PGC.…”
mentioning
confidence: 99%